2016
DOI: 10.1038/nn.4307
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling promotes basal progenitor expansion and the growth and folding of the neocortex

Abstract: The unique mental abilities of humans are rooted in the immensely expanded and folded neocortex, which reflects the expansion of neural progenitors, especially basal progenitors including basal radial glia (bRGs, also called outer RGs) and intermediate progenitor cells (IPCs). Here, we show that constitutively active Shh signaling expanded bRGs and IPCs and induced folding in the otherwise smooth mouse neocortex, whereas the loss of Shh signaling decreased the number of bRGs and IPCs and the size of the neocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
150
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 55 publications
16
150
0
Order By: Relevance
“…Constitutive activation of Shh signaling achieved by expressing a constitutively active form of Smo (SmoM2; [52]) in cortical progenitors in mid-corticogenesis, results in an increase in the proliferation of Tbr2+ IPs and promotes the expansion of basal RGs (bRGs) [53]. bRGs are neural progenitors that exist in very small numbers in the mouse but are a predominant progenitor population in the developing human neocortex [54, 55].…”
Section: Mitogenic Roles Of Shh Signaling In Cortical Progenitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Constitutive activation of Shh signaling achieved by expressing a constitutively active form of Smo (SmoM2; [52]) in cortical progenitors in mid-corticogenesis, results in an increase in the proliferation of Tbr2+ IPs and promotes the expansion of basal RGs (bRGs) [53]. bRGs are neural progenitors that exist in very small numbers in the mouse but are a predominant progenitor population in the developing human neocortex [54, 55].…”
Section: Mitogenic Roles Of Shh Signaling In Cortical Progenitorsmentioning
confidence: 99%
“…In humans and likely other primate species, Dlx2 and Ascl1 are highly expressed in the fetal proliferative zones of the neocortex and may generate a subpopulation of GABAergic interneurons [64–67]. Given the expansion of bRG progenitors in SmoM2-expressing cortical progenitors, human cortical progenitors could have also acquired the ability to generate GABAergic interneurons partially due to increasing Shh signaling activity observed in the fetal human neocortex [53]. Indeed, detectable Shh mRNA is observed in the proliferative outer SVZ (where bRGs are largely localized), RG progenitors, and early post-mitotic neurons in the human fetal neocortex at mid-gestation (at ∼20 gestational weeks), a time of active cortical neurogenesis [53, 68, 69].…”
Section: Roles Of Shh Signaling In the Specification Of Cortical Progmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also suggest that local expansion of OSVZ progenitors through increased generation or self-renewal may contribute to early stereotyped folding of the cortical plate (de Juan Romero et al, 2015; Dehay et al, 1996; Dehay et al, 1989; Dehay et al, 2001; Florio et al, 2015; Kriegstein et al, 2006; Nonaka-Kinoshita et al, 2013; Stahl et al, 2013; Wang et al, 2016). In agreement with findings in the ferret cortex (Reillo and Borrell, 2012; Reillo et al, 2011), we observed fewer oRG cells underneath the human calcarine sulcus than the adjacent gyrus during mid-neurogenesis (Figure 4D).…”
mentioning
confidence: 99%
“…Constitutively active Shh signaling leads to higher proportion of bRGs and IPs, and enlarged brains and midline folding, which is similar to brain defects of Gli3 knockout mice (Rallu et al, 2002; Wang et al, 2016). Reports from us indicate that Gli3 regulates brain size and midline cortical structure, which is potentially through modulating the Shh signaling as either an activator or a suppressor.…”
Section: Discussionmentioning
confidence: 85%